Improvement of Soil Bearing Capacity Using Bamboo Technology - Nawawi, Muhammad Ezzul Ehsan; Zainorabidin, Adnan (Recent Trends in Civil Engineering and Built Environment, 2023)
In some cases, for construction, the engineering performance of the soil at the site may not meet the requirements according to the design. This factor can be identified during the site investigation phase of the project. Soil such as clay can be a hassle to deal with during and also after the construction as the settlement process can be lengthy and might be ongoing until the project is already finished. This will lead to problems to the structure such as cracking for buildings and also for pavements. This study will emphasize the improvement of soil bearing capacity using other methods which are more sustainable. Bamboo is a viable alternative due to its physical and mechanical properties which can withstand a high degree of load without failing. In order to prove the suitability of bamboo to be used as a soil improvement option, an on-field test will be carried out to compare the results of soil with bamboo and soil without bamboo.